Training Program in Siwungkuk 01 Elementary School to Improve Skills Teaching - Muhamad Lutfi Hakim; Laelia Nurpratiwiningsih (ASEAN Journal of Empowering Community, 2021)
In carrying out his professional duties, a teacher is obliged as follows. First, planning to learn, carrying out quality learning processes, and assessing and evaluating learning outcomes. Second, improving and developing academic qualifications and competencies on an ongoing basis in line with science, technology, and the arts. Third, act objectively and non-discriminatory based on consideration of particular gender, religion, ethnicity, race, physical condition, family background, and socioeconomic status of learners in learning. Fourth, they uphold the laws, laws, codes of conduct of teachers, and religious and ethical values. One way to obtain and develop the four competencies for prospective teachers is the Field Experience Program (PPL). In general, the purpose of PPL is to condition (familiarize) students as candidates with all school life in real life. In particular, PPL aims to allow students to know, educate, train, and understand directly and carefully about the following. Know the physical environment, administration and school environment, and its discipline carefully. Owning and mastering essential learning. Able to carry out teaching skills on learning activities to be taught. Have a professional standard of teacher complementary. It shaped students' personalities as qualified educators and professionals, mastering and applying the principles of teaching science. The way for Guiding students towards the formation of a person is who has the value of knowledge and skills needed in the shape of proposed as an educational force.